Reprezentacija spola pri prejemnikih nagrade kresnik - Žunkovič, Igor (Slavistična revija, 2017)
The present study analyzes features of the main literary characters, drawing on the referential study of gender properties of literary characters by Jonathan Gottschall in his Literature, Science, and a New Humanities. The referential methodological layout has been adapted to the needs of the analysis of modern prose vis-a-vis Gottschall's traditional tales. The goal of the study is to explicate the gender and gender-related properties of literary characters in the selected population of modern Slovene novels. The secondary goal is a comparison with Gottschall's results and a critical review of his conclusions on the appropriateness of feminist and evolutionary views and on the causes of potentially differing representations of genders in literature. Last but not least, the author compares the results and methodology of the present study with other gender-related studies of literary characters in contemporary Slovene novels.
Keywords: "Literature, science, and the new humanities"; feminism; feminizem; Gottschall, Jonathan, 1921-2005; kresnik; kvantitativne študije; literarna teorija; literarne nagrade; literary theory; študije spola; teorija revolucije